A modified carbon nitride photocatalytic composite material and its preparation method and application
By covalently grafting asymmetric A2B2 porphyrin molecules with S-C3N4 to form a D(p-Br)PP/S-C3N4 composite photocatalyst, the existing carbon nitride photocatalysts have been solved, and the photocatalytic efficiency of existing carbon nitride photocatalysts in the visible light region is achieved, and the efficient photocatalytic degradation effect is achieved, and the stability of the material is improved.
Patent Information
- Application Number
- CN202410555604.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-07
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-05-07
AI Technical Summary
The existing carbon nitride photocatalysts have low absorption and photocatalytic efficiency in the visible light zone, and there is a risk of environmental pollution.
By synthesizing asymmetric A2B2 porphyrin molecules 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin (D(p-Br)PP) and S-C3N4 to form a D(p-Br)PP/S-C3N4 composite photocatalyst, significantly improving the absorption and photocatalytic efficiency of S-C3N4 in the visible light region.
The absorption and photocatalytic efficiency of S-C3N4 in the visible light zone is significantly improved, and the degradation effect of antibiotics in wastewater is significantly improved. At the same time, the stability is better due to the formation of new compounds.
Smart Images

Figure CN118341483B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalytic composite materials, and in particular to a modified carbon nitride photocatalytic composite material and a preparation method and application thereof. Background Art
[0002] In recent years, the modification research of S-C3N4 has focused on morphology and structure regulation and metal-based inorganic semiconductors. However, inorganic photocatalysts also have some limitations, including high price, poor visible light response, and the risk of secondary environmental pollution caused by metal elements. Therefore, organic semiconductor photocatalysts have attracted more and more attention due to their low cost, strong visible light absorption capacity, environmental friendliness, good biocompatibility and abundant raw material resources.
[0003] Therefore, how to provide a modified carbon nitride photocatalytic composite material and its preparation method and application to improve the absorption and photocatalytic efficiency of S-C3N4 in the visible light region is a difficult problem to be solved urgently in this field. Summary of the invention
[0004] In view of this, the present invention provides a modified carbon nitride photocatalytic composite material and a preparation method and application thereof to improve the absorption and photocatalytic efficiency of S-C3N4 in the visible light region.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] A method for preparing a modified carbon nitride photocatalytic composite material comprises the following steps:
[0007] 1) mixing p-bromobenzaldehyde, pyrrole and a first catalyst, and reacting to obtain 5-(4-bromophenyl)dipyrromethane;
[0008] 2) mixing 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachloro-p-benzoquinone and an organic solvent, and reacting to obtain 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin;
[0009] 3) 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin, S-C3N4, an organic phosphine ligand, a second catalyst, an organic base and an organic solvent are mixed and reacted to obtain a modified carbon nitride photocatalytic composite material.
[0010] Preferably, in step 1), the mass volume ratio of p-bromobenzaldehyde, pyrrole and the first catalyst is 2-4 g: 50-100 mL: 0.1-1 g.
[0011] Preferably, the reaction time in step 1) is 5 to 7 hours;
[0012] The first catalyst includes indium chloride.
[0013] Preferably, in the step 2), the mass volume ratio of 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachlorobenzoquinone and organic solvent is 0.5-0.7 g: 0.1-0.3 g: 0.1-0.4 mL: 0.6-0.8 g: 100-300 mL.
[0014] Preferably, the reaction time in step 2) is 3 to 5 hours;
[0015] The organic solvent in step 2) includes one or more of dichloromethane, chloroform and ethyl acetate.
[0016] Preferably, in the step 3), the mass volume ratio of the total mass of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin and S-C3N4, the organic phosphine ligand, the second catalyst, the organic base and the organic solvent is 150-250 mg: 5-15 mg: 5-15 mg: 300-500 mg: 20-40 mL;
[0017] The mass ratio of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin to S-C3N4 is 1-3:7-19.
[0018] Preferably, the reaction temperature in step 3) is 90-120° C., and the reaction time is 6-8 hours.
[0019] Preferably, the organic phosphine ligand in step 3) includes 1,1'-binaphthyl-2,2'-bisdiphenylphosphine;
[0020] The second catalyst is bis(dibenzylideneacetone)palladium;
[0021] The organic base includes one or more of sodium tert-butoxide, sodium ethoxide and sodium amide;
[0022] The organic solvent in step 3) includes one or more of 1,4-dioxane, pyridine and methyl ethyl ketone.
[0023] Another object of the present invention is to provide a modified carbon nitride photocatalytic composite material prepared by the above preparation method.
[0024] Another object of the present invention is to provide a modified carbon nitride photocatalytic composite material for use in photocatalytic degradation of organic wastewater.
[0025] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:
[0026] The invention synthesizes an asymmetric A2B2 porphyrin molecule 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin (D(p-Br)PP), and bonds it with S-C3N4 by a covalent grafting method to synthesize a D(p-Br)PP / S-C3N4 composite photocatalyst. Based on the characteristics of the asymmetric A2B2 porphyrin molecule, the invention can couple S-C3N4 and the porphyrin molecule to significantly improve the absorption and photocatalytic efficiency of S-C3N4 in the visible light region. The invention forms a new compound by using a macrocyclic organic matter and C3N4 to increase the conjugated system, thereby increasing the photocatalytic performance, and plays a role in the efficient degradation of antibiotics in sewage. Since it is a single new compound, it is different from the general inorganic heterojunction and has better stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0028] Figure 1 The spectrum detection results of S-C3N4, Examples 1 to 2 and Comparative Example 1;
[0029] Figure 2 XRD diagram of S-C3N4 and the modified carbon nitride photocatalytic composite material prepared in Example 1;
[0030] Figure 3 The fluorescence intensity test results of S-C3N4 and the modified carbon nitride photocatalytic composite materials prepared in Examples 1 to 4;
[0031] Figure 4 The UV-visible spectra of the modified carbon nitride photocatalytic composite material prepared in Examples 1 to 4 for degradation of tetracycline hydrochloride are shown in FIG. Figure 4 a in corresponds to Example 1, Figure 4 b in corresponds to Example 2, Figure 4 c in the embodiment 3 corresponds to Figure 4 d in corresponds to Example 4;
[0032] Figure 5 This is a graph showing the degradation efficiency of tetracycline hydrochloride by the modified carbon nitride photocatalytic composite material prepared in Examples 1 to 4;
[0033] Figure 6 The free radical capture experiment diagram of the modified carbon nitride photocatalytic composite material prepared by the present invention for degradation of tetracycline hydrochloride;
[0034] Figure 7 Fluorescence intensity change diagram of the reaction system, where Figure 7 a in the figure is a graph showing the change in fluorescence intensity corresponding to the addition of the modified carbon nitride photocatalytic composite material prepared by the present invention. Figure 7 Figure b is the fluorescence intensity change graph corresponding to the photocatalytic composite material without adding modified carbon nitride. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a modified carbon nitride photocatalytic composite material, comprising the following steps:
[0036] 1) mixing p-bromobenzaldehyde, pyrrole and a first catalyst, and reacting to obtain 5-(4-bromophenyl)dipyrromethane;
[0037] 2) mixing 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachloro-p-benzoquinone and an organic solvent, and reacting to obtain 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin;
[0038] 3) 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin, S-C3N4, an organic phosphine ligand, a second catalyst, an organic base and an organic solvent are mixed and reacted to obtain a modified carbon nitride photocatalytic composite material.
[0039] In the present invention, the mass volume ratio of p-bromobenzaldehyde, pyrrole and the first catalyst in step 1) is 2-4g:50-100mL:0.1-1g, preferably 2.1-3g:55-80mL:0.1-0.5g, and more preferably 2.12g:60mL:0.2g.
[0040] In the present invention, the reaction time in step 1) is 5 to 7 hours, specifically 5.2 hours, 5.5 hours, 6 hours, 6.2 hours, and 6.5 hours.
[0041] In the present invention, the first catalyst includes indium chloride, and the first catalyst also includes corresponding hydrates, such as InCl3·4H2O and the like.
[0042] In the present invention, the mass volume ratio of 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachlorobenzoquinone and organic solvent in step 2) is 0.5-0.7g: 0.1-0.3g: 0.1-0.4mL: 0.6-0.8g: 100-300mL, preferably 0.55-0.65g: 0.2-0.25g: 0.2-0.35mL: 0.7-0.78g: 150-250mL, and further preferably 0.6g: 0.21g: 0.3mL: 0.75g: 200mL.
[0043] In the present invention, the reaction time in step 2) is 3 to 5 hours, specifically 3.5 hours, 4 hours, or 4.5 hours.
[0044] In the present invention, the organic solvent in step 2) includes one or more of dichloromethane, chloroform and ethyl acetate.
[0045] In the present invention, the mass volume ratio of the total mass of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin and S-C3N4, the organic phosphine ligand, the second catalyst, the organic base and the organic solvent in the step 3) is 150-250 mg: 5-15 mg: 5-15 mg: 300-500 mg: 20-40 mL; preferably 180-220 mg: 8-12 mg: 8-12 mg: 350-450 mg: 25-35 mL; further preferably 200 mg: 10 mg: 10 mg: 400 mg: 30 mL.
[0046] In the present invention, the mass ratio of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin to S-C3N4 is 1-3:7-19, specifically 1:19, 2:18, 3:17, 3:7.
[0047] In the present invention, the reaction temperature in step 3) is 90-120°C, specifically 95°C, 100°C, 105°C, 110°C, 115°C; the reaction time is 6-8h, specifically 6.5h, 7h, 7.5h.
[0048] In the present invention, the organic phosphine ligand in step 3) includes 1,1'-binaphthyl-2,2'-bisdiphenylphosphine.
[0049] In the present invention, the second catalyst is bis(dibenzylideneacetone)palladium.
[0050] In the present invention, the organic base includes one or more of sodium tert-butoxide, sodium ethoxide and sodium amide; the function of the organic base is to provide a strong alkaline environment.
[0051] In the present invention, the organic solvent in step 3) includes one or more of 1,4-dioxane, pyridine and methyl ethyl ketone.
[0052] In the present invention, the reactions in steps 1) to 3) are preferably carried out under an inert atmosphere, which includes a nitrogen atmosphere or a rare gas atmosphere.
[0053] The present invention also provides a modified carbon nitride photocatalytic composite material prepared by the above preparation method.
[0054] The invention also provides an application of a modified carbon nitride photocatalytic composite material in photocatalytic degradation of organic wastewater.
[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] 1) Add p-bromobenzaldehyde (2.12 g), pyrrole (60 mL) and InCl3·4H2O (0.2 g) to a two-necked flask, evacuate with argon three times, and stir at room temperature for 6 h. After the reaction is completed, add NaOH (4 g) to quench the reaction and stir for another 45 min. Subsequently, add ethyl acetate to the reaction solution, wash the organic phase with water, collect the organic phase and add anhydrous Na2SO4 to dry, remove the solvent with a rotary evaporator, and obtain a brown oily substance, which is washed with ethyl acetate and distilled under reduced pressure to remove the solvent again. The resulting powder is recrystallized twice with ethanol aqueous solution to obtain a brown solid 5-(4-bromophenyl)dipyrromethane.
[0058] 2) At room temperature, 5-(4-bromophenyl)dipyrromethane (0.6 g) and benzaldehyde (0.21 g) were dissolved in CH2Cl2 (200 mL). After obtaining a uniform solution, trifluoroacetic acid (0.3 mL) was added, and the reaction mixture was stirred at room temperature for 3 hours, and then tetrachlorobenzoquinone (750 mg) was added and stirred for another 3 hours. After the reaction was completed, it was concentrated using a rotary evaporator, and the resulting mixture was separated and purified by column chromatography (filler: neutral alumina, eluent: CH2Cl2), and the resulting eluent was concentrated. The crude product was purified by silica gel column chromatography (CH2Cl2-n-hexane = 1:1) to obtain a purple-black solid 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin (D(p-Br)PP).
[0059] 3) 200 mg of S-C3N4 was ultrasonically dispersed in 30 mL of 1,4-dioxane for 20 min, and then D(p-Br)PP was added according to the mass ratio of D(p-Br)PP to S-C3N4 of 1:19 and then ultrasonically dispersed for 15 min. Then 10 mg of organic phosphine ligand 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 10 mg of catalyst bis(dibenzylideneacetone)palladium and sodium tert-butoxide (400 mg) were added to the obtained uniform suspension. The reaction system was protected by argon, and after evacuation and degassing three times, it was refluxed at 105°C for 7 h. After the reaction was completed, it was filtered and washed with water, and vacuum dried at 60°C for 12 h to obtain a D(p-Br)PP / S-C3N4 composite material with a D(p-Br)PP content (wt%) of 5%.
[0060] Example 2
[0061] The only difference between this embodiment and embodiment 1 is that the mass ratio of D(p-Br)PP and S-C3N4 is 1:9 (the total amount of D(p-Br)PP and S-C3N4 added is the same as in embodiment 1), and a 10% D(p-Br)PP / S-C3N4 composite material is obtained.
[0062] Example 3
[0063] The only difference between this embodiment and embodiment 1 is that the mass ratio of D(p-Br)PP and S-C3N4 is 3:17 (the total amount of D(p-Br)PP and S-C3N4 added is the same as that in embodiment 1), and a 15% D(p-Br)PP / S-C3N4 composite material is obtained.
[0064] Example 4
[0065] The only difference between this embodiment and embodiment 1 is that the mass ratio of D(p-Br)PP and S-C3N4 is 3:7 (the total amount of D(p-Br)PP and S-C3N4 added is the same as in embodiment 1), and a 30% D(p-Br)PP / S-C3N4 composite material is obtained.
[0066] Example 5
[0067] 1) Add p-bromobenzaldehyde (2 g), pyrrole (50 mL) and InCl3·4H2O (0.5 g) to a two-necked flask, purge with argon three times, and stir at room temperature for 5 h. After the reaction is completed, add NaOH (4 g) to quench the reaction and stir for another 45 min. Subsequently, add ethyl acetate to the reaction solution, wash the organic phase with water, collect the organic phase and add anhydrous Na2SO4 to dry, remove the solvent with a rotary evaporator, and obtain a brown oily substance, which is washed with ethyl acetate and distilled under reduced pressure to remove the solvent again. The resulting powder is recrystallized twice with ethanol aqueous solution to obtain a brown solid 5-(4-bromophenyl)dipyrromethane.
[0068] 2) Dissolve 5-(4-bromophenyl)dipyrromethane (0.7 g) and benzaldehyde (0.3 g) in CH2Cl2 (200 mL) at room temperature. After obtaining a uniform solution, add trifluoroacetic acid (0.1 mL), stir the reaction mixture at room temperature for 3 hours, then add tetrachlorobenzoquinone (600 mg), and continue stirring for 3 hours. After the reaction is completed, concentrate it with a rotary evaporator, and the resulting mixture is separated and purified by column chromatography (filler: neutral alumina, eluent: CH2Cl2), and the resulting eluent is concentrated. The crude product is purified by silica gel column chromatography (CH2Cl2-n-hexane = 1:1) to obtain a purple-black solid 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin (D(p-Br)PP).
[0069] 3) 150 mg of S-C3N4 was ultrasonically dispersed in 40 mL of 1,4-dioxane for 20 min, and then D(p-Br)PP was added according to the mass ratio of D(p-Br)PP to S-C3N4 of 1:19 and then ultrasonically dispersed for another 15 min. Then 12 mg of organic phosphine ligand 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 8 mg of catalyst bis(dibenzylideneacetone)palladium and sodium tert-butoxide (480 mg) were added to the obtained uniform suspension. The reaction system was protected by argon, and after evacuation and degassing three times, it was refluxed at 90°C for 8 h. After the reaction was completed, it was filtered and washed with water, and vacuum dried at 60°C for 12 h to obtain a D(p-Br)PP / S-C3N4 composite material with a D(p-Br)PP content (wt%) of 5%.
[0070] Example 6
[0071] 1) Add p-bromobenzaldehyde (4 g), pyrrole (100 mL) and InCl3·4H2O (1 g) to a two-necked flask, purge with argon three times, and stir at room temperature for 7 h. After the reaction is completed, add NaOH (4 g) to quench the reaction and stir for another 45 min. Subsequently, add ethyl acetate to the reaction solution, wash the organic phase with water, collect the organic phase and add anhydrous Na2SO4 to dry, remove the solvent with a rotary evaporator, and obtain a brown oily substance, which is washed with ethyl acetate and distilled under reduced pressure to remove the solvent again. The resulting powder is recrystallized twice with ethanol aqueous solution to obtain a brown solid 5-(4-bromophenyl)dipyrromethane.
[0072] 2) Dissolve 5-(4-bromophenyl)dipyrromethane (0.5 g) and benzaldehyde (0.12 g) in CH2Cl2 (250 mL) at room temperature. After obtaining a uniform solution, add trifluoroacetic acid (0.4 mL), stir the reaction mixture at room temperature for 3 hours, then add tetrachlorobenzoquinone (800 mg), and continue stirring for 3 hours. After the reaction is completed, concentrate it with a rotary evaporator, and the resulting mixture is separated and purified by column chromatography (filler: neutral alumina, eluent: CH2Cl2), and the resulting eluent is concentrated. The crude product is purified by silica gel column chromatography (CH2Cl2-n-hexane = 1:1) to obtain a purple-black solid 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin (D(p-Br)PP).
[0073] 3) 220 mg of S-C3N4 was ultrasonically dispersed in 25 mL of pyridine for 20 min, and then D(p-Br)PP was added according to the mass ratio of D(p-Br)PP to S-C3N4 of 1:19, and then ultrasonically dispersed for 15 min. 8 mg of organic phosphine ligand 1,1'-binaphthyl-2,2'-bisdiphenylphosphine, 8 mg of catalyst bis(dibenzylideneacetone)palladium and sodium tert-butoxide (300 mg) were added to the obtained uniform suspension. The reaction system was protected by argon, and after evacuation and degassing three times, it was refluxed at 90°C for 8 h. After the reaction was completed, it was filtered and washed with water, and vacuum dried at 60°C for 12 h to obtain a D(p-Br)PP / S-C3N4 composite material with a D(p-Br)PP content (wt%) of 5%.
[0074] Comparative Example 1
[0075] The purple-black solid D(p-Br)PP obtained in step 2) of Example 1 is used as Comparative Example 1.
[0076] Experimental Example 1
[0077] Spectral detection was performed on S-C3N4, Example 1, Example 2 and Comparative Example 1, and the detection results are as follows: Figure 1 As shown (abscissa: wave number (cm -1 ), ordinate: transmittance (%)), from Figure 1 It can be seen that S-C3N4 is between 3000 and 3500 cm -1 The vibration peak at 812 cm corresponds to the stretching vibration peak of NH, while the -1 The absorption peak at 3000-3500cm corresponds to the out-of-plane bending vibration of the triazine ring of S-C3N4. The spectral characteristics of 5% D(p-Br)PP / S-C3N4 and 10% D(p-Br)PP / S-C3N4 composites are similar to those of S-C3N4, which further shows that the addition of D(p-Br)PP has no significant effect on the structure of S-C3N4. In the spectra of 5% D(p-Br)PP / S-C3N4 and 10% D(p-Br)PP / S-C3N4 composites, the absorption peak at 3000-3500cm -1 The NH stretching vibration peaks at 3000-3500 cm-1 all showed a blue shift, which was caused by the strong interaction between D(p-Br)PP and S-C3N4 after compounding. -1 The stretching vibration peak at 2925cm-1 changed from a double peak to a single peak, indicating that the primary amine group (–NH2) in S-C3N4 was transformed into a secondary amine (–NH), further indicating that D(p-Br)PP and S-C3N4 have been successfully composited. -1 and 2850cm -1 The stretching vibration peaks at correspond to the asymmetric and symmetric stretching vibrations of saturated C–H.
[0078] The XRD spectra of S-C3N4 and Example 1 are as follows Figure 2 As shown (abscissa: diffraction angle, ordinate: intensity), through Figure 2 It can be observed that the diffraction peaks of S-C3N4 at 13.1° and 27.5° correspond to the (100) and (002) crystal planes, respectively. In the 5% D(p-Br)PP / S-C3N4 composite material, only these two diffraction peaks appear, which indicates that the addition of D(p-Br)PP does not affect the crystal structure of S-C3N4.
[0079] The fluorescence intensity test results of Examples 1 to 4 and S-C3N4 are as follows Figure 3 As shown (abscissa: wavelength, ordinate: fluorescence intensity), through Figure 3 It can be seen that the fluorescence intensity of the composite materials prepared in Examples 1 to 4 has decreased to varying degrees, which indicates that surface sensitization modification of S-C3N4 can significantly reduce the recombination rate of photogenerated electrons and holes, and the separation and migration rate of photogenerated electrons and holes of 30% D(p-Br)PP / S-C3N4 composite material is the highest. It can be concluded that the 30% D(p-Br)PP / S-C3N4 composite material has the most obvious improvement in catalytic efficiency.
[0080] The photocatalytic performance of D(p-Br)PP / S-C3N4 was detected using a 350W xenon lamp as a visible light source. 30 mg of D(p-Br)PP / S-C3N4 prepared in Examples 1 to 4 was added to 30 mL of tetracycline hydrochloride solution. The mixed solution was placed in a carousel-type photocatalytic reaction device, and stirred for 30 minutes in the dark to reach adsorption equilibrium. Then, 3 mL of the suspension was taken from the mixed solution every 20 minutes and filtered with a 0.45 μm microporous filter membrane. The absorbance of the filtrate was measured with a UV-visible spectrophotometer. The degradation rate was calculated using formula (2-3), where A0 is the initial absorbance of the tetracycline hydrochloride solution, and A t is the absorbance of levofloxacin or tetracycline hydrochloride solution at different times.
[0081]
[0082] Test results such as Figure 4 As shown (abscissa: wavelength, ordinate: absorbance), Figure 4 a in corresponds to Example 1, Figure 4 b in corresponds to Example 2, Figure 4 c in the embodiment 3 corresponds to Figure 4 d in corresponds to Example 4; Figure 4 It can be seen that the degradation ability of tetracycline by catalysts in different proportions can be seen.
[0083] The photocatalytic performance of D(p-Br)PP / S-C3N4 was detected using a 350W xenon lamp as a visible light source. 30 mg of D(p-Br)PP / S-C3N4 and S-C3N4 prepared in Examples 1 to 4 were added to 30 mL of tetracycline hydrochloride solution respectively. The mixed solution was placed in a carousel-type photocatalytic reaction device, and stirred for 30 minutes in the dark to reach adsorption equilibrium. Then, 3 mL of the suspension was taken from the mixed solution every 20 minutes and filtered with a 0.45 μm microporous filter membrane. The absorbance of the filtrate was measured with a UV-visible spectrophotometer and the degradation rate was calculated. Then, a graph was drawn with time as the horizontal axis and the degradation rate as the vertical axis. The test results are shown in the figure. Figure 5 As shown, from Figure 5 The efficiency diagram of catalyst photodegradation at different D(p-Br)PP contents can be obtained, and the photodegradation efficiency of catalysts at different proportions can be seen.
[0084] In the process of tetracycline degradation by D(p-Br)PP / S-C3N4 prepared by the present invention, 1 mmol / L of isopropyl alcohol (IPA), p-benzoquinone (BQ) and EDTA-2Na were added respectively to the tetracycline solution to generate ·OH, ·O 2- , H + Capture and record the degradation efficiency. Figure 6 As shown (abscissa: no quencher, isopropyl alcohol (IPA), para-benzoquinone (BQ), disodium ethylenediaminetetraacetate (EDTA-NA); ordinate: degradation rate), by Figure 6 It can be seen that during the degradation process, H + Plays a major role, followed by O 2 - , the effect of ·OH is minimal.
[0085] During the degradation of tetracycline by D(p-Br)PP / S-C3N4 prepared by the present invention, the change in the fluorescence intensity of the solution was detected. The detection results are as follows: Figure 7 As shown in (abscissa: wavelength, ordinate: intensity), the change in solution fluorescence intensity when the catalyst is added is shown in Figure 7 a in the figure, and the fluorescence intensity change when no catalyst is added is shown in Figure 7 b. by Figure 7 It can be seen that with the extension of illumination time, the fluorescence peak signal continues to increase, indicating that ·OH is continuously produced in the reaction system of D(p-Br)PP / S-C3N4 composite material for degrading tetracycline hydrochloride.
[0086] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0087] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a modified carbon nitride photocatalytic composite material, characterized in that: The steps include: 1) mixing p-bromobenzaldehyde, pyrrole and a first catalyst, and reacting to obtain 5-(4-bromophenyl)dipyrromethane; 2) mixing 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachloro-p-benzoquinone and an organic solvent, and reacting to obtain 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin; 3) mixing 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin, S-C3N4, an organic phosphine ligand, a second catalyst, an organic base and an organic solvent, and reacting the mixture to obtain a modified carbon nitride photocatalytic composite material; In the step 1), the mass volume ratio of p-bromobenzaldehyde, pyrrole and the first catalyst is 2-4 g: 50-100 mL: 0.1-1 g; The reaction time in step 1) is 5 to 7 hours; The first catalyst includes indium chloride; In the step 2), the mass volume ratio of 5-(4-bromophenyl)dipyrromethane, benzaldehyde, trifluoroacetic acid, tetrachlorobenzoquinone and organic solvent is 0.5-0.7 g: 0.1-0.3 g: 0.1-0.4 mL: 0.6-0.8 g: 100-300 mL; In the step 3), the mass volume ratio of the total mass of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin and S-C3N4, the organic phosphine ligand, the second catalyst, the organic base and the organic solvent is 150-250 mg: 5-15 mg: 5-15 mg: 300-500 mg: 20-40 mL; The mass ratio of 5,15-bis(4-bromophenyl)-10,20-diphenylporphyrin to S-C3N4 is 1-3:7-19; The organic phosphine ligand in step 3) includes 1,1'-binaphthyl-2,2'-bisdiphenylphosphine; The second catalyst is bis(dibenzylideneacetone)palladium; The organic base includes one or more of sodium tert-butoxide, sodium ethoxide and sodium amide; The organic solvent in step 3) includes one or more of 1,4-dioxane, pyridine and methyl ethyl ketone.
2. The method for preparing a modified carbon nitride photocatalytic composite material according to claim 1, characterized in that: The reaction time in step 2) is 3 to 5 hours; The organic solvent in step 2) includes one or more of dichloromethane, chloroform and ethyl acetate.
3. A method for preparing a modified carbon nitride photocatalytic composite material according to claim 1 or 2, characterized in that: The reaction temperature in step 3) is 90-120° C., and the reaction time is 6-8 hours.
4. The modified carbon nitride photocatalytic composite material prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the modified carbon nitride photocatalytic composite material according to claim 4 in photocatalytic degradation of organic wastewater.
Citation Information
Patent Citations
Water-soluble porphyrin conjugated polymer as well as preparation method and application thereof
CN103755928A
Porphyrin sensitization carbon nitride photocatalyst for producing hydrogen peroxide and preparation method of photocatalyst
CN110102342A